(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2013)
The Spanish Constitution of 1812 attributes to the City Council and the Province institutions more relevance than any other Spanish constitutional text. This paper argues that, contrary to the opinion held by several authors, the regulation of the City Council and the Province in the Constitution of 1812 configures a State with some degree of decentralization. This decentralization is due, on the one hand, to political reasons relating to the European Spain, where a free City Council became a liberal political myth in the fight against the absolute monarchy; and, on the other, to political reasons related to the American Spain, where the provinces constituted the first step to the self-government and the decentralization of the power.